Development and Analysis of Performance Measurement Indicators Utilized by Third Party Logistics Service Providers - Pesonen, Veera (My University, 2021)
Performance is important part of a company’s operations as it describes how well company is fulfilling its goals. Supply chain and logistics connect the product to a consumer from the manufacturer via different actions and actors. Transportation is required from sourcing of raw material through production to the delivering of finished products to end users, as also seen in reverse logistics. This thesis combines these two aspects related to performance and its measurement in third-party logistics transportations. Performance and its measurement have been researched a lot but most of the time research are related to financial point of view. Environmental performance is usually used to measure performance in green logistics. Logistics performance together with environmental performance has not been research specially in third-party logistics. The focus in this thesis is to research performance from environmental and logistics point of view and especially have third-party logistics service providers as a main research area. Research question of this thesis is: What are the key performance indicators utilized by third-party logistics service providers in measurements? The objectives for this research question are to find out what performance indicators and key performance indicators third-party logistics service providers use in their transportations environmental and logistics measurements. In addition, objectives include to finding out why are these indicators chosen. Last objective is to develop and propose alternative solutions for performance measurement and indicators. This research is based on qualitative interview with an open-ended questionnaire as the data collection method. The interview has been built around theoretical framework what has been formed from central findings of the literature review. Literature review is consisted of three parts which cover the main topics of the study which are third-party logistics service providers, performance measurement and performance indicators. The interview was conducted with one company, so the sample size is 1 as questions were answered from a company-wide perspective. The results showed that the significance of company goals is major in performance measurement and indicators as company goals guides indicators selection. Instead importance of performance measurement system in indicators selection can be stated to be quite minor. Results also pointed out environmental performance to be highlighted in performance measurement and especially in performance indicators.

Suorituskyky on tärkeä osa yritysten toimintaa, sillä se kuvaa kykyä suoriutua tavoitteiden toteuttamisessa. Toimitusketju ja logistiikka yhdistävät tuotteen valmistajalta kuluttajalle eri toimijoiden ja toimintojen avulla. Kuljetuksilla on avainrooli toimitusketjussa ja logistiikassa sillä kuljetuksia tarvitaan useisiin eri toimintoihin tuotannon alusta aina tuotteen toimittamiseen loppuasiakkaalle kuin myös paluulogistiikkaan. Tämä tutkimus yhdistää nämä kaksi aspektia ja tutkii tekijöitä, jotka liittyvät suorituskykyyn ja sen mittaamiseen kolmannen osapuolen logistiikan kuljetuksissa. Suorituskykyä ja sen mittaamista on tutkittu paljon, mutta useimmiten tutkimukset ovat olleet talouden näkökulmasta. Ympäristön suorituskyvyn mittaukset ovat yleensä kohdistuneet vihreään logistiikkaan. Logistista suorituskykyä yhdessä ympäristön suorituskyvyn kanssa ei ole tutkittu erityisesti kolmannen osapuolen logistiikassa. Tämän vuoksi tutkimuksen pääpaino on suorituskyvyn mittaaminen erityisesti ympäristön ja logistiikan näkökulmasta ja keskittyen erityisesti kolmannen osapuolen logistiikan palveluntarjoajiin. Tämän tutkimuksen tutkimuskysymys on: Mitkä ovat tärkeimmät suorituskykyindikaattorit, joita kolmannen osapuolen logistiikkapalvelujen tarjoajat käyttävät mittauksissa? Kysymyksen tavoitteena on saada selville mitä ympäristön ja logistiikan suorituskyvyn indikaattoreita kolmannen osapuolen logistiikkapalvelujen tarjoajat käyttävät ja mitkä niistä ovat avainindikaattoreita. Lisäksi tavoitteena on selvittää, miksi nämä indikaattorit on valittu sekä tehdä kehitysehdotuksia suorituskyvyn mittaamiseen ja indikaattoreihin. Tämä tutkimus on laadullinen tutkimus, jossa datankeräysmetodina on avoimia kysymyksiä sisältävä haastattelu. Haastattelu on rakennettu teoreettisen viitekehyksen ympärille, joka taas on muodostettu kirjallisuuskatsauksen keskeisimmistä löydöksistä. Kirjallisuuskatsaus koostuu kolmesta osasta, jotka kattavat tutkimuksen pääaiheet. Nämä osat ovat kolmannen osapuolen logistiikan palveluntarjoajat, suorituskyvyn mittaaminen ja suorituskyvyn indikaattorit. Haastattelu toteutettiin yhden yrityksen kanssa ja kysymyksiin vastasi yksi työntekijä koko yrityksen näkökulmasta, joten tutkimuksen otoskoko on 1. Tutkimuksen tulokset osoittavat, että yrityksen tavoitteiden merkitys on suuri suorituskyvyn mittaamisessa ja indikaattoreissa, sillä nämä tavoitteet ohjaavat indikaattoreiden valintaa. Sen sijaan suorituskyvyn mittausjärjestelmien merkitys indikaattoreiden valinnassa jäi hieman epäselväksi. Lisäksi tulokset osoittivat ympäristön suorituskyvyn korostuvan suorituskyvyn mittaamisessa logistiseen suorituskykyyn nähden.
Keywords: fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management